Možnosti uporabe sistema Nintendo za vadbo za ravnotežje kot dodatek fizioterapiji pri starostnikih - Zupanc, Aleksander (Rehabilitacija (Ljubljana), 2015)
Elderly persons face perceptual and physical changes, as well as cognitive changes related to learning and slower perception of information. Provided that it is entertaining, the training with the Nintendo system motivates the elderly person for physical activity. The training affects physical, psychological and social activities of the elderly. It is advisable for balance training as an addition to physiotherapy. The Nintendo system can be used in clinical environment, as well as for community-dwelling elderly or within the home environment for independent training. Wii Fit games must be selected according to the physical and cognitive abilities of the elderly person.
Keywords: Aged; balance training; ravnotežje; ravnotežna plošča Wii; starostniki; telesna vadba; vadba za ravnotežje; Wii balance board; Wii Fit games; Wii Fit igre